2020
DOI: 10.1002/jmri.27452
|View full text |Cite
|
Sign up to set email alerts
|

Flow Volume Loop and Regional Ventilation Assessment Using Phase‐Resolved Functional Lung (PREFUL) MRI: Comparison With 129Xenon Ventilation MRI and Lung Function Testing

Abstract: Background Regional flow volume loop ventilation‐weighted noncontrast‐enhanced proton lung MRI in free breathing has emerged as a novel technique for assessment of regional lung ventilation, but has yet not been validated with 129Xenon MRI (129Xe‐MRI), a direct visualization of ventilation in healthy volunteers, cystic fibrosis (CF), and chronic obstructive pulmonary disease (COPD) patients. Purpose To compare regional ventilation and regional flow volume loops measured by noncontrast‐enhanced ventilation‐weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 40 publications
(51 reference statements)
0
43
0
Order By: Relevance
“…Recently, 2D PREFUL VDP was validated to hyperpolarized 129 Xe imaging with very promising results. 23 Future studies are necessary to address the mentioned limitations.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, 2D PREFUL VDP was validated to hyperpolarized 129 Xe imaging with very promising results. 23 Future studies are necessary to address the mentioned limitations.…”
Section: Limitationsmentioning
confidence: 99%
“…Repeatability and validation studies of 2D PREFUL to reference standards have been performed to facilitate the use of 2D PREFUL in clinical routine. [20][21][22][23] Recently, 3D PREFUL has been developed to assess dynamic ventilation of the whole lung in an 8-minute acquisition, and the preliminary feasibility results in 16 study participants including patients with asthma, CF, and COPD have been presented. 24 However, the repeatability of ventilation parameters derived from 3D PREFUL, which is necessary to know prior to its use in clinical settings, has not been assessed.…”
mentioning
confidence: 99%
“…Spatial and quantitative biomarker agreement with hyperpolarized gas MRI have been some of the primary goals of functional 1 H lung MRI development to date 4–6 . In this issue of JMRI, Kaireit et al 7 derived PREFUL MRI regional ventilation as well as regional flow‐volume loop maps and compared with 129 Xe MRI static ventilation and clinical lung function tests. Multiple PREFUL metrics were generated, but the primary assessment was the ventilation defect percent (VDP) for both PREFUL and 129 Xe.…”
mentioning
confidence: 99%
“…A unique addition of this work 7 was the regional comparison of PREFUL regional ventilation and flow‐volume loop with 129 Xe ventilation defects. This analysis suggested that the combination of PREFUL flow‐volume loop with regional ventilation approaches may be more sensitive to partially obstructed or slow‐filling lung units.…”
mentioning
confidence: 99%
See 1 more Smart Citation